The Expansion of "Private" Schools in England, Sweden and Eastern Germany: A Comparative Perspective on Policy Development, Regulation, Policy Goals and Ideas. Issue 5 (20th October 2017) - West, Anne; Nikolai, Rita
Abstract: In a diverse range of European countries, there has been an increase in the proportion of pupils attending schools owned by private bodies but funded by the state. This article compares the policy development and governance of private government-dependent schools in three countries/regions: England, Sweden and Berlin/Brandenburg in Eastern Germany. It is found that the regulatory frameworks vary and are associated with specific policy goals and ideas, with apparently similar ideas having different meanings. It is also found that the growth of private government-dependent schools is related to policy goals, differing institutional configurations and political parties.